LEVEL OF ADOLESCENT KNOWLEDGE ABOUT PREMARITAL SEX IN GUBUKUSUMA VILLAGE, TIDORE ISLANDS CITY - Sinta Muhammad, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Adolescence is a critical period in a person's life, because there is a transition period from a child to an adult. One of the factors of sexuality problems in adolescents is hormonal changes that increase sexual desire (libido, sexuality) in adolescents. This increase in sexual desire requires channeling in certain forms of behavior. The distribution could not be carried out immediately due to the delay in the marriage age. Further, adolescents will develop further sexual desire for other behaviors such as kissing and masturbation. The tendency is increasing due to the dissemination of information and sexual stimulation through the mass media which with the existence of advanced technology becomes unstoppable for those who are in a period of curiosity and want to try sexual behavior. This study is a descriptive research with a cross sectional method. The population in this study is adolescents in Gubukusuma Village, Tidore Islands City with a sample of 53 people. The results of the study showed that the level of knowledge of adolescents in the category of deficient was 28 people (53%). The importance of health education about reproductive health for adolescents to behave sexually healthy.